The Influence of Silent Sitting and Mindful Parenting on Interest in Learning The Students of STIAB Jinarakhita Lampung - Burmansah; Andriyaningsih, Ayu; Sutawan, Komang; Rapiadi; Sumarwan, Edi (LPPM STIAB JINARAKKHITA LAMPUNG, 2023)
The research aims to find out the influence of silent sitting and mindful parenting on the interests of students of STIAB Jinarakkhita Lampung. In the research there are some problems, among others, there are still students who do not pay attention to the lecturer when explaining, there is still a student who does not collect lectures, still there are students who don't answer questions when asked by the teacher, and there are also students who talk to my cousins when the lecturers explain the lectures in class this indicates that there is a problem related to the interests of learning. The methodology used is descriptive quantitative research. The subject in this study is a student of the Buddhist Religious Education study program with a total of 45 Students. The sample in this study is as many as 30 people. Data collection techniques in this study include using interviews and lifts. (kuisioner). This study uses a double linear regression analysis with a degree of error of 5%. R square or R2=0.940=94%. The value shows that the variation of student learning interest variables (Y) can be explained by the variable silent sitting (X1) and mindful parenting (X2) combined at 94%. In other words, the variables silent siting (x1) and Mindful Parenting (x2) influence the student interest variable (y) by 94% and the remaining 6% are influenced by other factors that are not included in this study model. (Y). Based on data analysis, it can be concluded that 1) there is a simultaneous influence between silent sitting and mindful parenting on learning interests. 2) This shows that the more positive silent sitting and the higher mindful parenthood, the more will increase the interest of students of STIAB Jinarakkhita Bandar Lampung.